Dragon ball Z. 1 - Toriyama, Akira, 1955-; Jones, Gerard, 1957- (Shonen Jump manga., 2008)
Collects the first three volumes of the "Dragonball Z" manga, in which Goku and his friends battle the evil Saiyans, who seek to destroy the Earth.